Current Status of Cancer Diagnosis and Treatment in Nigeria - Tolulope Joseph Ogunniyi; Boluwatife Samuel Fatokun; Kafayat Omolara Isah; Asmau Abdulbaki; Adeola Roqeebat Emiola; Kesaobaka Batisani (Health Science Reports)
ABSTRACT Introduction Cancer has emerged as a leading cause of death worldwide, surpassing HIV/AIDS, tuberculosis, and malaria combined. Nigeria's cases and deaths continue to increase every year due to the high cancer burden that affects the country. There were 269,109 new cancer cases registered in 2022, with breast and prostate cancer being the most prevalent. Despite improvements made, several problems related to the diagnosis and treatment of cancer across the nation remain. This paper reviews these issues while discussing what is being done to establish an efficient system for managing cancer care in Nigeria. Methods This review utilizes publicly available sources such as GLOBOCAN, Google Scholar, PubMed, and other gray literature. The search was focused on challenges and efforts regarding the diagnosis and treatment of cancers, using Nigeria as one of the main filters. Results In the review, substantial obstacles to diagnosing and treating cancer in Nigeria included insufficient diagnostic equipment, high out‐of‐pocket healthcare costs, as well as delayed diagnosis due to the unavailability of health information and service delivery. With only 27 cancer treatment centers available for a population of 218.5 million people, patients encounter delays as well as financial burdens. Efforts have been made, such as establishing cancer centers, launching the Cancer Health Fund, and introducing policies to improve screening and treatment accessibility, like the National Strategic Cancer Control Plan. Also, the Nigerian Sovereign Investment Authority (NSIA) and Lagos University Teaching Hospital (LUTH) Cancer Treatment Centre, from its inauguration in 2019–2024, has treated more than 10,064 patients, providing 8528 radiotherapies, 6733 chemotherapies, and 215 high‐dose rate 3D brachytherapy sessions, revitalizing an industry previously unable to adequately address cancer in Nigeria. Conclusion Nigeria still faces immense challenges in improving cancer diagnosis and treatment. Although recent initiatives are encouraging, enhanced policies and funding are still needed. The provision of more diagnostic services, awareness concerning various types of cancers, and an increase in treatment facilities will be vital to improving cancer care in Nigeria.